저추력 추진기를 활용한 초소형위성체계 배치형상 획득을 위한 제어 방법론 - 김하은; Ha-eun Kim; 김상일; Sang-il Kim; 이성섭; Soung-sub Lee (한국항행학회논문지, 2024)
현재 우리 군은 북한의 위협뿐만 아니라 다양한 전방위 위협에 신속하게 대응할 수 있는 지휘 통제 체계를 구축하기 위해 초소형위성체계 사업을 추진하고 있다. 본 논문에서는 저추력의 전기추진시스템인 홀추력기를 사용하여 초소형 군집위성 배치 형상을 획득하기 위한 비선형 제어기법을 제시한다. 제어기법은 일반적인 리야프노프(Lyapunov)의 제어 이론의 적용과 전기추진기의 on-off 제어를 위한 분석적 해법에 의해 구해지며 궤도 6요소 중 장반축만을 제어하여 위성군의 궤도 형상을 효과적으로 배치할 수 있는 기법이다. 본 연구에서 개발된 제어기법은 초소형위성체계에 적용하기위해 안정성을 검증하고 결과를 분석한다. Currently, the Korean military is promoting a small satellite system project to establish a command and control system that can quickly respond to various threats from all directions, not only from North Korea. In this paper, we present a nonlinear control law to acquire the geometry of a small cluster satellite deployment using a low-thrust electric propulsion system, the Hall thruster. The control law is obtained by applying the general Lyapunov’s control theory and analytical solution for the on-off control of the electric thruster, and it is a technique that can effectively deploy the orbital configuration of the satellite constellation by controlling only the semi-major axis of the six elements of the orbit. In this study, the stability of the developed control law is verified and the results are analyzed for application to a very small satellite system.